Shaping the Discourse around Quality EdTech in India: Including Contextualized and Evidence-Based Solutions in the Ecosystem - Leena Bhattacharya; Minu Nandakumar; Chandan Dasgupta; Sahana Murthy (MDPI AG, 2024)
This paper examines the extent to which an initiative in India, namely EdTech Tulna, has been able to move towards decolonization of EdTech by shaping the discourse around the adoption and use of good quality and contextual educational technology solutions for Indian learners. Set up as a collaboration among researchers, practitioners, teachers and governments, EdTech Tulna aims to encourage the selection of EdTech solutions that are appropriate for the community they are designed for, rather than adopting solutions that market themselves or those that have been successful in Western countries. The paper adopts the lens of justice-oriented design and first critically examines the design of the EdTech Tulna index. Then, it examines the success and hurdles of the collaborative efforts towards the implementation of contextualized and evidence-based solutions in the ecosystem. By analyzing stakeholder interviews and meeting notes, this paper addresses two questions. First, how does Tulna assist in identifying quality contextual solutions that are likely to enhance the learning of children in India? Second, how do state government officials and practitioners collaborate with researchers to use research-based standards for selecting such solutions? The discussions outline the progress and draw a broad contour of the road ahead.